Towards a new Eastern Mediterranean Energy Corridor? Natural gas developments between market opportunities and geopolitical risks - Simone Tagliapietra (Fondazione Eni Enrico Mattei (FEEM), 2013)
The Eastern Mediterranean region is rapidly changing. The turbolent political transition in Egypt after the Arab Spring, the civil war in Syria, the emergence of Turkey as leading regional power, the tensions between Israel and Gaza and the never-ending dispute between Turkey and the Republic of Cyprus are -all together- reshuffling the regional geopolitical equilibrium. At the same time natural gas findings are flourishing in the offshore of Egypt, Israel, and Cyprus, reshaping the regional energy map and rapidly making the Eastern Mediterranean a world-class natural gas province. These geopolitical and energy pressures are rapidly converging, generating a number of new challenges and opportunities for each player in the region. The aim of this paper is to provide a comprehensive overview on these new regional developments and to propose a critical discussion of the market opportunities and geopolitical risks related to the potential emergence of a new Eastern Mediterranean Energy Corridor.
Keywords: Q40; Q42; Q48; 330; Eastern Mediterranean; natural gas; energy geopolitics; Turkey; Israel; Egypt; Cyprus; Lebanon; European Union; security of gas supply; energy security